2020
DOI: 10.1186/s12934-020-01302-7
|View full text |Cite
|
Sign up to set email alerts
|

Production of riboflavin and related cofactors by biotechnological processes

Abstract: Riboflavin (RF) and its active forms, the cofactors flavin mononucleotide (FMN) and flavin adenine dinucleotide (FAD), have been extensively used in the food, feed and pharmaceutical industries. Modern commercial production of riboflavin is based on microbial fermentation, but the established genetically engineered production strains are facing new challenges due to safety concerns in the food and feed additives industry. High yields of flavin mononucleotide and flavin adenine dinucleotide have been obtained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 139 publications
1
84
0
Order By: Relevance
“…The formation of reduced compounds such as lactic acid, ethanol, and butanol, among others, is evidence of the occurrence of metabolic pathways shifting from acidgenesis to solventogenesis [ 43 ]. One intermediate (I-1), a primary α-hydroxy ketone with butan-2-one substituted by a hydroxy group at positions 1 and 3 or a secondary α-hydroxy ketone, has a close structural analogue of 3,4-dihydroxybutan-2-one, whose phosphorylated form ( l -3,4-dihydroxybutan-2-one 4-phosphate) is a precursor for the synthesis of riboflavin [ 47 ]. Formyl 7 E -hexadecenoate, an effective nitrogen removal stimulant found in aquatic duckweed, was reported in lactic acid bacteria enhanced fermented milk [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The formation of reduced compounds such as lactic acid, ethanol, and butanol, among others, is evidence of the occurrence of metabolic pathways shifting from acidgenesis to solventogenesis [ 43 ]. One intermediate (I-1), a primary α-hydroxy ketone with butan-2-one substituted by a hydroxy group at positions 1 and 3 or a secondary α-hydroxy ketone, has a close structural analogue of 3,4-dihydroxybutan-2-one, whose phosphorylated form ( l -3,4-dihydroxybutan-2-one 4-phosphate) is a precursor for the synthesis of riboflavin [ 47 ]. Formyl 7 E -hexadecenoate, an effective nitrogen removal stimulant found in aquatic duckweed, was reported in lactic acid bacteria enhanced fermented milk [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic engineering strategies based on the riboflavin metabolic pathway of B. subtilis are usually based on optimization of the central carbon metabolism, overexpression and deregulation of the RF synthesis and purine biosynthesis pathways, as well as blocking the synthesis of by-products [ 52 ]. The precursor supply in the RF biosynthesis pathway can be enhanced by redirecting the carbon flux through the PPP (pentose phosphate pathway) from the EMP (Embden-Meyerhof-Parnas) pathway, and increasing the expression of purine biosynthesis genes ( pur operon), thus increasing GTP production [ 53 , 54 ]. The yield of riboflavin in fed-batch fermentation using B. subtilis reached up to 826.52 mg/L [ 54 ].…”
Section: Vitamins As High-value Productsmentioning
confidence: 99%
“…Riboflavin biosynthesis begins from two major substrates, GTP and Ribu5P, derived from purine biosynthesis or/and the pentose phosphate pathway, containing seven enzymatic steps generating the final product ( Liu et al, 2020 ). Research on riboflavin biosynthesis demonstrated that characteristic features of most enzymes and steps involved in the riboflavin pathway are mostly similar between prokaryotes and plants, whereas fungi use a somewhat different pathway and enzymes ( Abbas and Sibirny, 2011 ).…”
Section: Biosynthesis Of Riboflavin and Its Derivativesmentioning
confidence: 99%